FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR - FLORIAN WULANDARI HADI; IRWANTO HANDOJO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The objective of this research is to obtain empirical evidence of auditor size, leverage, company growth, company size, institutional ownership, managerial ownership and company agesas independent variables to audit quality as dependent variable in Indonesian manufacturing companies.The research period is three years from 2012-2014 and population in this research is all listed companies in Indonesian Stock Exchange. Samples are obtained through purposive sampling method, which only 65 of listed manufacturing companies in Indonesian manufacturing companies meet the sampling criteria, resulting 195 data. Multiple linear regressions and hypothesis testing are used as the data analysis method in this research. The result of this research shows that leverage statistically have effect on the audit quality. While auditor size, company growth, company size, institutional ownership, managerial ownership and company ages have no effect on audit quality.